Interesting Life Journey of a Type 1 Diabetes Individual from the Era of Injectable Insulins to the Hybrid Closed-Loop Insulin Pump - Varun Anil Damle; Anandakumar Amutha; Munnavar Lovelena; Viswanathan Mohan (Journal of Diabetology)
Continuous subcutaneous insulin infusion (CSII) pump has shown good outcomes in individuals with diabetes. An individual with type 1 diabetes (T1D) was diagnosed in 1996 at the age of 14 years with GAD-positive and absent C Peptide reserves confirming the diagnosis. Initially, the individual was started with the conventional treatment for T1D consisting of multiple insulin injections per day, however, with this treatment, there was a wide fluctuation in the blood sugar levels with frequent hyperglycemic and hypoglycemic episodes, and could not achieve strict HbA1c control. In 2019, the treatment was switched to a 620G CSII pump, the fluctuations in blood sugar levels were reduced, but still, there were occasional hyperglycemic and hypoglycemic episodes failing to achieve the target HbA1c control. In 2022, again the treatment was changed to the latest 780G CSII pump termed the artificial pancreas which helped the person with T1D to achieve strict blood sugar level control and excellent ‘Time in Range’ with no hyperglycemic and hypoglycemic episodes and a better quality of life.